2020
DOI: 10.1080/00313831.2020.1761446
|View full text |Cite
|
Sign up to set email alerts
|

School-Contextual Paths to Student Bullying Behaviour: Teachers Under Time Pressure are Less Likely to Intervene and the Students Know It!

Abstract: We assessed whether the level of time-pressure reported by a school's teachers is predictive of student bullying perpetration. We combined data from two surveys conducted in 129 schools in 2016: the Stockholm School Survey performed among students in grades 9 and 11 (n = 10,668), and the Stockholm Teacher Survey carried out among senior level (grades 7-9) and upper secondary school (grades 10-12) teachers (n = 2259). Multilevel path analyses showed that teachers' stress and time-pressure increased with declini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…As características desse fenômeno são: a intencionalidade nos atos, a concordância no alvo sobre o que os agressores pensam a seu respeito e a presença do público ou espectadores. Apesar do Bullying poder ocorrer em diversos cenários, no ambiente escolar, entre os adolescentes, tal fenômeno ocorre com mais intensidade, em detrimento as instabilidades inerentes as grandes mudanças físicas, emocionais, sociais e psicológicas (Rajaleid, Brolin & Modin, 2020).…”
Section: Discussionunclassified
“…As características desse fenômeno são: a intencionalidade nos atos, a concordância no alvo sobre o que os agressores pensam a seu respeito e a presença do público ou espectadores. Apesar do Bullying poder ocorrer em diversos cenários, no ambiente escolar, entre os adolescentes, tal fenômeno ocorre com mais intensidade, em detrimento as instabilidades inerentes as grandes mudanças físicas, emocionais, sociais e psicológicas (Rajaleid, Brolin & Modin, 2020).…”
Section: Discussionunclassified
“…Overall, these articles establish that leaders and leadership styles influence employee (or pupils') health. Whereas a number of these articles conclude that leadership affects employee or workplace health in general [59,64,65,28,73], others are meant to explain what types of leadership are beneficial to health in the workplace. On the one hand, three articles covered transformational leadership's effects, concluded that this leadership type is suitable for countering bullying in the workplace [38], and contributed to an optimal effort-reward balance [61].…”
Section: Leadership's Role In Employee Healthmentioning
confidence: 99%
“…While the prevalence and detrimental effects of bullying behavior among students in schools are well-documented, there is a gap in understanding how a spiritual approach can be effectively integrated into educational settings to address and mitigate such behavior (Rajaleid et al, 2020). Specifically, the research problem explores school teachers' perspectives regarding the feasibility, impact, challenges, and potential strategies of employing a spiritual approach to counter bullying behavior among students.…”
Section: Introductionmentioning
confidence: 99%